Investigating the affecting factors on quality of life in informal settlements’ neighborhoods, with an emphasis on the Islamabad neighborhood in Zanjan - Kamran, Jalal (Ciência e Natura, 2015)
The importance of quality of life due to the direct impact on the urban community and system has been the subject of study by experts in various fields. In this regard, urban poor neighborhoods due to Inappropriate quality of life is one of challenges faced by the managers, urban planners, sociologists and other related fields. Urban poor neighborhoods as informal settlements due to the informal nature or considering informal, is the location of the poor which has always been in the improper status of the quality of life’s indices (like housing, literacy and education, income, environment, etc.). Assessment and evaluations of the quality of life in informal settlements’ neighborhoods are one of the most important studies of the empowerment project of these neighborhoods, which its result can be taken into account in providing sound solutions with regard to the quality of life in the mentioned neighborhoods. This paper examines and assess the quality of life in informal settlements’ neighborhoods by using two way of library research (theoretical framework) and Field research (collecting statistical data and questionnaires) on the Islamabad in Zanjan as a Case study and try to offer the cooperative strategies to increase quality life.